ATX-LPA axis facilitates estrogen-induced endometrial cancer cell proliferation via MAPK/ERK signaling pathway - Zhang, Guo (Mol Med Rep, 2018)
Autotaxin (ATX) is a key enzyme that converts lysophosphatidylcholine to lysophosphatidic acid (LPA). ATX is a crucial factor that facilitates cancer progression; however, the effect of ATX on endometrial cancer has not been explored. The aim of the present study was to investigate the role of ATX in the progression of endometrial cancer. The immunohistochemical results revealed higher protein expression levels of ATX and LPA receptors (LPA 1, 2 and 3) in human endometrial cancer tissue than in non-carcinoma tissue. In addition, reverse transcription-quantitative polymerase chain reaction and western blotting analysis demonstrated that ATX and LPA receptor mRNA and protein expression was greater in Ishikawa cells, which are positive for estrogen receptor (ER), than in Hec-1A cells that exhibit low ER expression. Short interfering RNA knockdown of ATX in Ishikawa cells led to decreased cell proliferation and cell colony number, as determined by Cell Counting kit-8 and colony formation assays. Estrogen stimulated ATX mRNA expression. Inhibition of ATX decreased estrogen and LPA-induced cell proliferation. High LPA levels markedly elevated the phosphorylation levels of extracellular signal-regulated kinase (ERK). ATX downregulation moderately decreased estrogen- and LPA-induced phosphorylation of ERK. In addition, the ERK inhibitor, PD98059, reduced cell proliferation with estrogen, ATX and LPA treatment. The present study suggested that the ATX-LPA axis may facilitate estrogen-induced cell proliferation in endometrial cancer via the mitogen-activated protein kinase/ERK signaling pathway. The present study may provide ideas and an experimental basis for clinicians to identify new molecular targeted drugs for the treatment of endometrial cancer.